2012
DOI: 10.1080/13607863.2011.638904
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors, course, and outcome of depression among older primary care patients: The PROSPECT study

Abstract: Objectives We sought to examine whether there are patterns of evolving depression symptoms among older primary care patients that are related to prognostic factors and long-term clinical outcomes. Method Primary care practices were randomly assigned to Usual Care or to an intervention consisting of a depression care manager offering algorithm-based depression care. In all, 599 adults 60 years and older meeting criteria for major depression or clinically-significant minor depression were randomly selected. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Once these risk factors are controlled, the relationship between age and depressive symptoms becomes non-significant. 12 Other studies have found several distinct patterns of LLD depressive symptoms over time, including high or low levels of persistent symptoms, 21 or remitting, intermittent, and chronic courses, 13 with variations by age and birth cohort. 15 These studies demonstrate the variability and diversity in patient experiences of LLD.…”
Section: Prevalence and Patterns Of Lldmentioning
confidence: 98%
“…Once these risk factors are controlled, the relationship between age and depressive symptoms becomes non-significant. 12 Other studies have found several distinct patterns of LLD depressive symptoms over time, including high or low levels of persistent symptoms, 21 or remitting, intermittent, and chronic courses, 13 with variations by age and birth cohort. 15 These studies demonstrate the variability and diversity in patient experiences of LLD.…”
Section: Prevalence and Patterns Of Lldmentioning
confidence: 98%
“…Two previous trajectory class analyses of depressive symptoms among older primary care patients have included cognitive measures in the analyses, but did not find cognition to be a significant predictor of trajectory class membership [15,26] . Cui et al [26] also included a specific assessment of executive functions in their study.…”
Section: Cognitionmentioning
confidence: 99%
“…Previous studies have reported results from trajectory analyses in different settings for DLL [1,[13][14][15][24][25][26][27][28][29] . However, few such studies have included hospitalized older patients in specialist health care services for old age psychiatry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on follow-up interviews, a positive response to any of these conditions was considered a chronic medical condition. Consistent with prior publications, 21 persons with 3 or more conditions were considered to have high medical burden.…”
Section: Methodsmentioning
confidence: 74%